Compact eighth‐mode ridged substrate integrated waveguide filter - Liguo Liu (Wiley, 2021)
Abstract In this letter, a novel eighth‐mode ridged substrate integrated waveguide (EMRSIW) is proposed by bisecting the RSIW resonator along the virtual magnetic walls. The EMRSIW shows a size of nearly one‐eighth of a conventional RSIW resonator and a significant size reduction compared to the conventional eighth‐mode SIW resonator. A prototype of a third‐order bandpass filter with transmission zeros has been designed and tested.